Chronic intermittent hypoxia aggravates intrahepatic endothelial dysfunction in cirrhotic rats12. Issue 4 (8th April 2013) - Hernández‐Guerra, Manuel; de Ganzo, Zaida Adrián; González‐Méndez, Yanira; Salido, Eduardo; Abreu, Pedro; Moreno, Miguel; Felipe, Vanesa; Abrante, Beatriz; Quintero, Enrique
Abstract Chronic intermittent hypoxia (CIH) occurs with obstructive sleep apnea syndrome (OSAS) and provokes systemic endothelial dysfunction, which is associated with oxidative stress and low nitric oxide (NO) bioavailability. Cirrhotic livers exhibit intrahepatic endothelial dysfunction, which is characterized by an impaired endothelium‐dependent response to vasodilators and hyperresponse to vasoconstrictors. We hypothesized that CIH may also contribute to intrahepatic endothelial dysfunction in cirrhosis. Normal and cirrhotic rats were exposed for 14 days to repetitive cycles of CIH mimicking OSAS in humans, or caged with room air (handled controls [HC]). Hepatic endothelial function was assessed in isolated and perfused rat livers by dose‐response curves to acetylcholine (ACh) and methoxamine (Mtx). In a group of cirrhotic rats, in vivo systemic and hepatic hemodynamic parameters were evaluated at baseline and after volume expansion. In addition, liver samples were obtained to assess endothelial nitric oxide synthase (eNOS), phosphorylated eNOS (p‐eNOS), NO bioavailability, and nitrotyrosinated proteins as a marker of oxidative stress. Cirrhotic rats exposed to CIH exhibited an attenuated vasodilatory response to ACh and hyperresponse to Mtx compared with HC rats. During volume expansion, similar portal pressure increases were observed in CIH and HC rats, although the mean arterial pressure increase was lower after CIH. These functional responses were associated with the presence of increased hepatic oxidative stress without changes in p‐eNOS after CIH exposure. In normal rats, no hemodynamic changes were found. Conclusion: CIH exacerbates intrahepatic endothelial dysfunction in cirrhotic rats, which is associated with increased oxidative stress that may reduce NO bioavailability. Clinical studies are needed to assess whether OSAS contributes to endothelial impairment in human patients with cirrhosis. (HEPATOLOGY 2013;57:1564–1574)